P139 Women's Health Care during COVID-19. (8th April 2021) - Rimmer, Michael P; Al Wattar, Bassel A; Barlow, Catriona; Black, Naomi; Carpenter, Ciara; Conti-Ramsden, Frances; Dalton, John A W; Davies, Rhianna; Davies, Rebecca; Dunlop, Cheryl; Guyett, Elvena; Jamison, Laura; et al.
Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic is disrupting health services worldwide. Women's health care is often acute and in continual demand, with poor health outcomes seen in women's health in particular in the recent Ebola and Swine flu epidemics. Regrettably, early reports globally and in the UK have shown a rise in the stillbirth rate. We aimed to evaluate the provision of obstetrics and gynaecology services in the UK during the acute phase of the COVID-19 pandemic. Methods: We undertook an interview-based national survey of junior doctors in obstetrics and gynaecology in women's healthcare units in the National Health Service using the network of the UK Audit and Research Collaborative in Obstetrics and Gynaecology. We sought responses on general training, labour ward care, antenatal and postnatal care, benign gynaecology and gynaecology oncology services. Results: We received responses from 148/155 units (95%) contacted. Most completed speciﬁc training drills for managing obstetric and gynaecological emergencies (89/148, 60.1%) and two-person donning and dofﬁng of personal protective Equipment (PPE) (96/148, 64.9%). The majority of surveyed units implemented COVID-19-speciﬁc protocols (130/148, 87.8%), offered adequate PPE (135/148, 91.2%) and operated dedicated COVID-19 emergency theatres (105/148, 70.8%). Most units suspended elective gynaecology services (131/148, 88.5%). The 2-week referral pathway for oncological gynaecology was not affected in half of the units (76/148, 51.4%), but half reported a planned reduction in oncology surgery (82/148, 55.4%) Discussion: Women's health care services have responded well to the acute phase of the COVID-19 pandemic, however further planning is required for the long term.